Influences of Bladders and Phase Change Materials in Anti-G Suit on Pilots' Thermal Responses (Journal of Fiber Bioengineering and Informatics, 2014)
A heat and humidity transfer model for the pilot wearing bladder anti-G garment system is developed.In the model, an 85-node human thermoregulatory model is developed for predicting pilots' thermalstresses and the coupled heat and humidity transfer equations including latent heat sorption/release ofthe Phase Change Materials (PCM) are utilized for the garment. Meanwhile, the garment inner boundaryconditions are treated by considering the bladder effects. Also, the model is validated by comparing thesimulation with experimental results. After the validation, water vapour concentration and temperatureat different parts of garment and evaporation heat loss, dry heat loss and skin temperature at differentparts of body are predicted and compared to study the influences of bladder. Otherwise sweat rate, sweataccumulation, mean skin temperature and comprehensive index of thermal stress under garments withdifferent volumetric fractions of PCM are also predicted and compared to study the influences of PCM.The conclusion shows that bladders will produce more heat stress on wearers and PCM can improve thethermal performance of the bladder anti-G garment.
Keywords: Bladder anti-G Garment; PCM; Human Thermoregulatory Model; Thermal Stress